Elaboración de una mermelada a base de remolacha Beta vulgaris y cereza Prunus avium libre de conservantes químicos, bajo condiciones de laboratorio. - Villao Vera, Isabel Alexandra (2024)
This work was carried out in the Agroindustry Laboratory of the Faculty of Agricultural Sciences of the Technical University of Babahoyo, located at Km 7.5 of the Babahoyo – Montalvo road, province of Los Ríos. The design that was applied in this research was experimental, that is, with manipulation and control of the variables. The completely randomized block experimental design was used in an AXB factorial arrangement with 3 treatments and 3 repetitions, where factor A is the raw materials and factor B is the sweeteners. To carry out the sensory analysis of beet and cherry jam: 70:30, 60:40; 50:50, with two different sweeteners, one caloric (brown sugar) and the other non-caloric (stevia). The Ordering or Ranking Test was used for the parameters of: flavor, color and texture, the same one that was applied to 20 tasters. untrained from the different careers of the Faculty of Agricultural Sciences. The physical-chemical and bromatological properties are determined for the best treatment. Through the analysis of the results it is assumed that the best treatment Beet (50%) + Cherry (50%) + stevia (60 gr) + brown sugar (40 gr) presented an acceptance based on the flavor: very pleasant from 17.33 people tasters untrained. The best treatment presents acceptable physical-chemical parameters according to the NTE INEN 419 Standards: pH 3.4, °Brix 60 and acidity 1.2. The jam based on Beet (50%) + Cherry (50%) + stevia (60 gr) + brown sugar (40 gr) has a greater amount of sugars due to the dosage applied. Percentages greater than 50% of beet and cherry limit consumer organoleptic acceptance. The Beet (50%) + Cherry (50%) + stevia (60 gr) + brown sugar (40 gr) jam has adequate nutritional potential with respect to the bromatological analysis carried out: Carbohydrates 60.8%, Ashes 0.8%, Fats 0.2%. Humidity 37.5% and Protein 0.7%, the same as those referenced with similar values evidenced in bibliographical works carried out.